How many lives are at stake? Assessing 2030 sustainable development goal trajectories for maternal and child health. (15th February 2018) - McArthur, John W; Rasmussen, Krista; Yamey, Gavin
Abstract : John W McArthur, Krista Rasmussen, and Gavin Yamey examine how far countries have to go to meet the targets for maternal and child mortality and what needs to be done to help them